UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN DI SEKOLAH DAN MENGAJAR DI KELAS MELALUI PENERAPAN REWARDAND PUNISHMENT DI SMPK RENHA ROSARI KEWAPANTE - Anggraini Tandjung Agustina (Yayasan Akrab Pekanbaru, 2019)
This study aims to improve teacher discipline in school attendance and teaching in the classroom through the application of reward and punishment to SMPK Renha Rosari Kewapante teachers. The method used in this study is the School Action Research (PTS) method which consists of 2 cycles. This research was conducted in one of the target schools, namely Renha Rosari Middle School, Kewapante Sikka Regency. The subjects of this study were all 22 teachers. Data collection techniques from school action research is through qualitative data obtained from observations, observations, and interviews. Analysis of the data used in this study is the analysis of qualitative data sourced from primary and empirical data. The results of the study can be obtained, namely: 1) The delay in the indicators of teachers coming to school cycle I as many as 12 people with a percentage of 54.55% and teachers who are late entering classes in teaching, as many as 18 teachers or 81.81%. 2) The delay of teachers in the indicators coming to school cycle II as many as 4 people or 18.09% and teachers who are late entering the class in teaching as many as 6 teachers or 27.28%. So it can be concluded that the application ofardard and punishment can improve teacher discipline in attendance to school and in the classroom in the teaching-learning process.